Molybdenum(iv) dithiocarboxylates as single-source precursors for AACVD of MoS2 thin films. Issue 33 (1st August 2022) - Muhammad, Saleh; Ferenczy, Erik T.; Germaine, Ian M.; Wagner, J. Tyler; Jan, Muhammad T.; McElwee-White, Lisa
Abstract : Deposition of MoS2 from Mo(S2 CMe)4 demonstrates use of dithiocarboxylate ligands for sulfur in single source precursors for TMD materials. Abstract : Tetrakis(dithiocarboxylato)molybdenum(iv ) complexes of the type Mo(S2 CR)4 (R = Me, Et, i Pr, Ph) were synthesized, characterized, and prescreened as precursors for aerosol assisted chemical vapor deposition (AACVD) of MoS2 thin films. The thermal behavior of the complexes as determined by TGA and GC-MS was appropriate for AACVD, although the complexes were not sufficiently volatile for conventional CVD bubbler systems. Thin films of MoS2 were grown by AACVD at 500 °C from solutions of Mo(S2 CMe)4 in toluene. The films were characterized by GIXRD diffraction patterns which correspond to a 2H-MoS2 structure in the deposited film. Mo–S bonding in 2H-MoS2 was further confirmed by XPS and EDS. The film morphology, vertically oriented structure, and thickness (2.54 μm) were evaluated by FE-SEM. The Raman E 1 2g and A1g vibrational modes of crystalline 2H-MoS2 were observed. These results demonstrate the use of dithiocarboxylato ligands for the chemical vapor deposition of metal sulfides.